Hidden People, Hidden Identity: socio-cultural and Linguistic change among Quechua migrants in lowland Bolivia - Martínez-Acchini, Leonardo Miguel (2017)
A dissertation presented to the graduate school of the University of Florida in partial fulfillment of the requirements for the degree of Doctor of Philosophy. 2009